CRIME REPORTING AND THE POSITIVE ROLE OF MEDIA IN CRIMINAL INVESTIGATIONS - Nana Vasadze (Innovate Conferences, 2025)
Reporting crime is one of the core functions of modern journalism. The media records and disseminates information, and acts as a bridge between law enforcement agencies and the public. Though the media is often criticized, its supportive role in identifying suspects, locating missing persons, and informing the public is significant and merits closer examination.The media can rapidly circulate images of suspects, crime scene details, and missing person notices. News coverage can reach distant audiences within minutes, thereby mobilizing public awareness and engagement. As Kania (2018) states, "Media coverage is often the first public response to criminal activity."